THE EFFECT OF AGRICULTURAL FUTURES PRICE CHANGES ON THE AGRICULTURAL PRODUCTION IN AP VOJVODINA - Živkov, Dejan; Papić-Blagojević, Nataša; Lončar, Sanja (Economics of Agriculture, 2019)
This paper investigates whether global agricultural futures of corn, wheat, oats, soybean and canola have any influence on the annual agricultural production of these plants in AP Vojvodina. For the estimation purposes, the study applies robust Bayesian quantile regression. Besides, two scenarios are considered – 1) current futures prices, and 2) futures prices from the previous year. Estimated results suggest that current futures prices do not affect current agricultural production of corn, wheat, oats and soybean in AP Vojvodina, because the estimated quantile parameters have negative sign or they are very small. However, when futures prices from the previous year are analysed, the majority of estimated QR parameters bear positive sign, which means that Serbian farmers take into account in greater or lesser extent the global agricultural prices when they plan their annual agricultural plantation. According to the findings, canola futures have the greatest effect on the rising Serbian canola production.